Performace of mango-ginger (Curcuma amada Roxb.) under different levels of shade - NAIR, B K JAYACHANDRAN, G SREEKANDAN (Journal of Spices and Aromatic Crops, 1998)
Field trials on the performance of mango-ginger (Curcuma amada) conducted at Vellayani (Kerala, India) for two seasons under varying levels of shade revealed that rhizome yield under open and 25 per cent shade were on par indicating that the crop is shade tolerant and is suitable for intercropping situations.